Commercial Woodfuel Production : Experience from Three Locally Controlled Wood Production Models - World Bank (Washington, DC, 2014)
Woodfuels (firewood and charcoal) are the dominant energy source and the leading forest product for most developing countries. Representing 60 to 80 percent of total wood consumption in these nations, woodfuels often account for 50 to 90 percent of all energy used. Although woodfuels are widely perceived as cheap and primitive sources of energy, commercial woodfuel markets are frequently very large, involve significant levels of finance, and provide an important source of income through the supply chain for the rural poor. However, the woodfuel sector in many developing countries operates informally and inefficiently, using out-dated technology and delivering little official revenue to the government. The unsustainable harvesting of woodfuels to supply large urban and industrial markets can also contribute to forest degradation and deforestation. Given the low carbon development opportunity presented by wood energy, predictions of significant growth in woodfuel demand make it vital that this industry is overhauled and modernized using new technologies, approaches, and governance mechanisms. This report profiles three promising models of commercial forestry that can contribute to modernization and rationalization of the wood energy sector in developing countries: (i) community-based forest management (CBFM), (ii) private woodlots in Sub-Saharan Africa, and (iii) forest replacement associations (FRA) in Latin America.